(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Engineering rheology in the food industry, as an object of study, considers the behavior of raw materials and semi-finished products at the stage of stretching, compression and twisting. The processes of mechanical processing of dough are associated with the interaction of viscous-plastic raw materials (dough) with the working parts of machines, therefore, for effective mechanical processing of dough, it is necessary to take into account its viscosity, plasticity, elasticity and other rheological properties. This will optimize the processes of mixing, rolling, forming and other operations, increasing productivity and quality of the final product. In addition, analysis of the rheological properties of the dough allows you to optimize the choice of equipment, optimal operating parameters (for example, rotation speed of working bodies, pressure and temperature), as well as the development of special processing technologies for various types of dough. In this regard, this work examines the determination of the compression force, the inertial component of the total resistance force, the force and pressure of the end resistance when fastening dough layers using a rotating roller.